1997
DOI: 10.1016/s0014-5793(97)01260-x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and cyclic AMP act at different levels on transcription of the L‐type pyruvate kinase gene

Abstract: We previously demonstrated that, in hepatocytes in primary culture, the role of insulin on induction of L-type pyruvate kinase (L-PK) gene expression was mainly to induce glucokinase synthesis, needed for glucose phosphorylation to glucose 6-phosphate. However, we show here that when hepatocytes have been isolated from rats starved for 72 h, glucose and constitutive glucokinase expression was not sufficient to fully stimulate the L-PK promoter, low insulin concentrations being still required. In addition, acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…As previously reported [14–21], the −183PK construct was stimulated by glucose about seven‐fold and inhibited by cAMP about 11‐fold. The glucose‐dependent stimulation was also totally abolished by cotransfection with the PKA expression vector (Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…As previously reported [14–21], the −183PK construct was stimulated by glucose about seven‐fold and inhibited by cAMP about 11‐fold. The glucose‐dependent stimulation was also totally abolished by cotransfection with the PKA expression vector (Fig.…”
Section: Resultssupporting
confidence: 85%
“…Transcription of the L‐PK gene is stimulated by glucose and inhibited by glucagon acting through its second messenger, cAMP. The inhibition of the L‐PK gene by cAMP was shown to involve the classical PKA signaling pathway since the cAMP effect could be reproduced by overexpression of the PKA catalytic subunit [21]. We have previously shown that the in vivo transcriptional inhibition by glucagon of glucose responsive genes in the liver was a very rapid phenomenon, detectable in only a few minutes by run‐on transcription assays [1], contrasting with the activation by glucose which is delayed for several hours [23].…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of cAMP levels by glucagon, insulin, and catecholamines accounts in large part for minute-to-minute hormonal control of pathway flux in fed animals and during the transition from fed to starved. cAMP plays a key role in the regulation of gene transcription of gluconeogenic and lipolytic enzymes: it enhances the transcription of genes encoding hepatic enzymes, such as PEPCK, which in turn induces glucose production (7,30) and negatively regulates the transcription of L-PK gene, a key enzyme of glycolysis (5). In the liver, GK activity is regulated at the level of gene transcription in response to fasting and refeeding (15,22), and its transcription is negatively regulated by glucagon through increases in cAMP concentration (13,14,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…5) gene transcription in the liver of the F28 mice compared with Co mice might be caused by the increased hepatic basal adenylyl cyclase activity. cAMP is known to negatively regulate the L-PK gene transcription (5,14). The decreased L-PK gene transcription is consistent with a decreased glycolytic flux and fits the strongly increased expression of the gluconeogenetic enzyme PEPCK (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…At this level, the expression of genes for GK, 6PFK2/FBP2, 6PFK1, and PK are stimulated by either glucose or insulin [32,33], whereas expression of genes for PEPCK, FBPase, and G6Pase are repressed [34,35]. Fasting reverses these changes that suppress HGP during feeding.…”
Section: Regulation Of Hepatic Glucose Productionmentioning
confidence: 99%